2014
DOI: 10.1002/dta.1719
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the misuse of cobalt in horses

Abstract: Cobalt is a well-established inducer of hypoxia-like responses, which can cause gene modulation at the hypoxia inducible factor pathway to induce erythropoietin transcription. Cobalt salts are orally active, inexpensive, and easily accessible. It is an attractive blood doping agent for enhancing aerobic performance. Indeed, recent intelligence and investigations have confirmed cobalt was being abused in equine sports. In this paper, population surveys of total cobalt in raceday samples were conducted using ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(100 citation statements)
references
References 27 publications
1
92
1
6
Order By: Relevance
“…Knych et al [41] , Ho et al [42] Ho et al [42] Nickel Schaumloffel et al [44] --Xenon, krypton -Thevis et al [48] -…”
Section: Gnrhunclassified
See 1 more Smart Citation
“…Knych et al [41] , Ho et al [42] Ho et al [42] Nickel Schaumloffel et al [44] --Xenon, krypton -Thevis et al [48] -…”
Section: Gnrhunclassified
“…[41] The study suggested that regulators should be able to detect administration of a single dose of cobalt to horses. Ho et al [42] conducted an extended study in which the proposed threshold concentrations of 2 ug/L in plasma and 75 ug/L in urine could be used as control limits for the detection of cobalt in horses on race-days. As recommended, a dose of minimum daily cobalt intake for horses through dietary supplements has been reported.…”
Section: Cobaltmentioning
confidence: 99%
“…It is important that we continue with the development of technologies and assays to detect and control the misuse of cobalt in horses (Ho et al, 2015) and remain prepared to review and refine the urinary and plasma threshold concentrations based on emerging new evidence. If this disturbing trend continues and more unexplained deaths occur, we must focus new research on the effects of physiologically relevant concentrations of cobalt chloride on global patterns of gene expression, protein function and cytotoxicity in primary equine cells and tissues in vitro, make predictions about its bioavailability and pathophysiological effects in vivo and develop sensitive biomarkers to examine its effects on the myocardium.…”
Section: The Concernmentioning
confidence: 99%
“…Cobalt chloride is a well-established hypoxia mimetic and inducer of hypoxia-like responses, which can cause gene modulation at the hypoxia inducible factor pathway to stimulate EPO transcription and increase its levels in blood (Ho et al, 2015). Cobalt (symbol Co, atomic number 27) is a transition metal in the periodic table.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation